Olaparib Conjugates with Selenopheno[3,2-c]quinolinone Inhibit PARP1 and Reverse ABCB1-Related Multidrug Resistance - Marina Makrecka-Kuka; Jelena Vasiljeva; Pavels Dimitrijevs; Pavel Arsenyan (MDPI AG, 2022)
The restoration of the efficacy of antitumor medicines is a cornerstone in the combat with multidrug resistant (MDR) cancers. The overexpression of the ABCB1 transporter is a major obstacle to conventional doxorubicin therapy. The synergy of ABCB1 suppression and PARP1 activity inhibition that hampers malignant cell DNA repair could be a powerful tool in anticancer therapy. Herein, we report the design and synthesis of three novel olaparib conjugates with selenophenoquinolinones, their ability to reverse doxorubicin resistance in uterus sarcoma cells as well as their mechanism of action. It was found that the most potent chemosensitizer among studied compounds preserves PARP1 inhibitory activity and attenuates cells' resistance to doxorubicin by inhibiting ABCB1 transporter activity. These results demonstrate that the conjugation of PARP inhibitors with selenophenoquinolinones is a prospective direction for the development of agents for the treatment of MDR cancers.